Influence of Training and Career Development on the Performance of Employees in the Stockfit Department at PT. Adis Dimension Footwear Tangerang - Marsiyah, Marsiyah; Purwanto, Agus; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The problem in this study is the suboptimal performance of employees in the Stockfit department at PT. Adis Dimension Footwear Balaraja-Tangerang, which is suspected to be caused by ineffective training and career development. One factor that can support employee performance is effective training and career development.The purpose of this study was to determine the influence of simultaneous training and career development on the performance of employees in the Stockfit department at PT. Adis Dimension Footwear Balaraja-Tangerang.This study used a quantitative descriptive method, which describes variables as they are, supported by numerical data generated from actual conditions. The population in this study was all employees in the production department at PT. Adis Dimension Footwear Balaraja-Tangerang. The research sample consisted of 84 respondents. This study used a saturated sampling technique due to the small population size; therefore, the entire population of 84 employees was used as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis using SPSS 26. Data validity was obtained through partial t-tests and simultaneous F-tests.The results of this study indicate that (1) partially, training significantly influences t on the performance of Stockfit employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value > t table (2.209 >1.990) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, career development significantly influences the performance of Stockfit employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value > t table (10.024 >1.990) and a significance value of 0.000 smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, training and career development significantly influence the employee performance of Stockfit employees at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by F count > F table (334.900 > 3.11) with a significance level of 0.000. Thus, Ha is accepted and H0 is rejected.Based on the research results, it can be concluded that training and career development variables, both partially and simultaneously, have a significant influence on the performance of Stockfit employees at PT. Adis Dimension Footwear Balaraja-Tangerang.